Environmental heterogeneity and population density affect the functional diversity of personality traits in small mammal populations. Issue 1940 (9th December 2020) - Mortelliti, Alessio; Brehm, Allison M.
Abstract : Understanding factors affecting the functional diversity of ecological communities is an important goal for ecologists and conservationists. Previous work has largely been conducted at the community level; however, recent studies have highlighted the critical importance of considering intraspecific functional diversity (i.e. the functional diversity of phenotypic traits among conspecifics). Further, a major limitation of existing literature on this topic is the lack of empirical studies examining functional diversity of behavioural phenotypes —including animal personalities. This is a major shortcoming because personality traits can affect the fitness of individuals, and the composition of personalities in a population can have important ecological consequences. Our study aims to contribute to filling this knowledge gap by investigating factors affecting the functional diversity of personality traits in wild animal populations. Specifically, we predicted that the richness, divergence and evenness associated with personality traits would be impacted by key components of forest structure and would vary between contrasting forest types. To achieve our objective we conducted a fully replicated large-scale field experiment over a 4 year period using small mammal populations as a model system. We found that greater heterogeneity in the cover of shrubs, coarse woody debris and canopy cover was associated with a greater richness, lower divergence and lower evenness in personality traits. Greater population density was associated with greater functional richness and lower functional divergence and evenness of personality traits. To maintain a behaviourally diverse population and its associated functions, managers may promote heterogeneity in vegetation and increased population density, which we found to be the most important determinants driving functional diversity of personality traits.